Chronic unpredictable mild stress induces anxiety-like behavior in female C57BL/6N mice, accompanied by alterations in inflammation and the kynurenine pathway of tryptophan metabolism - Luo, Yanqin; Jiang, Ning; Zhang, Yiwen; Zhao, Yongzhi; Chen, Fang; Li, Xueyan; Qiang, Meng; Zeng, Guirong; He, Qinghu; Liu, Xinmin; Shan, Chunhui (Frontiers in Neuroscience, 2025)
Chronic stress can impact brain function through various mechanisms, contributing to the development of anxiety disorders. Chronic unpredictable mild stress (CUMS) is a well-established model for studying the effects of chronic stress. This study assessed the impacts of different durations of CUMS on anxiety-like behavior, inflammation, and tryptophan metabolism in female C57BL/6N mice. The results revealed significant behavioral changes after 2–4 weeks of CUMS. Specifically, the open arms ratio and open arms time ratio in the elevated plus maze (EPM) decreased, the latency to feed in the novelty-suppressed feeding test (NSFT) was prolonged, and the number of transitions in the light/dark box (LDB) was decreased. After 1 week of CUMS, the levels of some pro-inflammatory cytokines (such as IL-1β and iNOS) and anti-inflammatory cytokines (including IL-10) began to rise. After 2 weeks of CUMS, most pro-inflammatory cytokines (IL-1β, IL-6, CD86, iNOS) and the anti-inflammatory cytokines TGF-β and CD11b showed an increase, while some anti-inflammatory cytokines (Arg-1, IL-10) began to decrease. After 3 weeks of stress, the pro-inflammatory cytokine TNF-α also significantly increased, while the anti-inflammatory cytokine TGF-β began to decline. By 4 weeks of CUMS, the anti-inflammatory cytokine CD11b also started to decrease. Regarding tryptophan metabolism, after 3–4 weeks of CUMS, serotonin (5-HT) levels in the hippocampus of the mice began to decrease. Additionally, the kynurenine pathway in tryptophan metabolism shifted more towards the KYN-QA branch, resulting in the reduction in the neuroprotective substance kynurenic acid (KYNA), while neurotoxic substances such as 3-hydroxykynurenine (3-HK) and quinolinic acid (QA) accumulated. In summary, female C57BL/6N mice exhibit anxiety-like behavior after 2 weeks of CUMS, accompanied by inflammatory responses. After 3–4 weeks of CUMS, anxiety-like behavior persists, with exacerbated inflammatory responses and disturbances in tryptophan metabolism.